A CIDADE DOS MORTOS NO MUNDO DOS VIVOS - OS CEMITÉRIOS (Revista de História Regional, 2007)
This article tries to present elements regardingthe way cemitery building has changed in time, as well as tpexplore some other functions of this holy space, particularlyin France.